The Role of Work Engagement as A Mediating Variable : The Effect of Authentic Leadership on Employee Career Satisfaction - Siti Nurhasanah; Kenni Roz (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
The hospitality industry, characterized by intensive customer interactions and dynamic service demands, places constant pressure on employees to maintain professionalism, adaptability, and the ability to deliver prompt and high-quality service. Within such a context, leadership emerges as a critical factor in sustaining long-term employee performance and organizational success. This study emphasizes authentic leadership as a leadership style capable of fostering positive employee attitudes while aligning individual aspirations with broader organizational goals. Authentic leaders promote constructive psychological conditions through self-awareness, balanced information processing, internalized moral values, and relational transparency, all of which are essential for nurturing trust and motivation in service-oriented environments.The primary objective of this research is to investigate the mediating role of work engagement in the relationship between authentic leadership and hotel employees’ career satisfaction. To achieve this, a quantitative approach was adopted, involving a survey of 100 hotel employees working in Malang, Indonesia. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both the direct and indirect relationships among the studied variables. The findings reveal that authentic leadership has a significant and positive influence on both work engagement and career satisfaction. Moreover, work engagement itself exerts a strong effect on career satisfaction and serves as a full mediator between authentic leadership and career satisfaction. These results contribute to the growing body of literature on leadership and employee outcomes by underscoring the strategic importance of authentic leadership in enhancing employees’ psychological resources, strengthening their engagement, and ultimately improving career satisfaction, which is indispensable for maintaining competitiveness in the hospitality sector.